Establishment and parameter calibration of the discrete element model for typical clay in hilly and mountainous areas - Chen, Fei; Yang, Li; Cui, Tao; Zhang, Dongxing; He, Xiantao; Zhang, Kailiang (International Journal of Agricultural and Biological Engineering, 2025)
The mechanism of the interaction between the furrow opener and clay is the basis for optimizing the performance of the furrow opener. However, there is currently a lack of discrete element simulation parameters that can accurately simulate the actual furrowing operation. This paper considers the combined influence of clay particle bonding and adhesion-wetness based on the Hertz-Mindlin with Bonding V2 (Bonding V2) and Hertz-Mindlin with JKR V2 (JKR V2) contact models. The contact parameters of the JKR V2 contact model between clay particles and between clay and the furrow opener were obtained through simulations and physical tests of the clay angle of repose (AOR), static friction between clay and the furrow opener, and rolling friction. The test results show that the normal/tangential stiffness per unit area has a greater impact on the simulation results of the clay compaction. The bonding parameters of the Bonding V2 contact model were determined by screening significant factors through Plackett-Burman (PB) tests, narrowing the range of significant parameters through steepest climb tests, and optimizing parameters through Box-Behnken Design (BBD) tests. Based on the results of the above tests, the accuracy of the Bonding V2 and JKR V2 contact models and the improvement over a single model were verified through direct shear soil simulation and physical tests. Based on the Bonding V2 and JKR V2 contact models and the multibody dynamics model of the furrow opener, the coupling simulation parameters of the seeder furrow operation were optimized to obtain the optimal furrow opening operation parameters under uphill and downhill conditions. Field tests further verified the simulation realism and feasibility of the Bonding V2 and JKR V2 contact models. The Bonding V2 and JKR V2 contact models for clay in hilly and mountainous areas (HAMA) can provide a reference for modeling clay in HAMA and simulating the contact between the furrow opener and other contact parts during the furrow opener operation. Keywords: DEM, Bonding V2 contact model, JKR V2 contact model, hilly and mountainous areas, clay, furrow opening, Parameter calibration DOI: 10.25165/j.ijabe.20251805.9794 Citation: Chen F, Yang L, Cui T, Zhang D X, He X T, Zhang K L. Establishment and parameter calibration of a discrete element model for typical clay in hilly and mountainous areas. Int J Agric & Biol Eng, 2025; 18(5): 26–38.